Influence of tool rotation rates on temperature profiles and mechanical properties of friction stir welded AZ31 magnesium alloy. Issue 5 (February 2017) - Wang, Weideng; Deng, Dean; Mao, Zhitao; Tong, Yangang; Ran, Yang
Abstract The influence of tool rotation rates on temperature profiles, microstructure, and mechanical properties of friction stir welded AZ31 magnesium alloys was investigated experimentally and numerically. AZ31 plates with a thickness of 8 mm were joined by friction stir welding process with five different rotation rates (from 800 to 1600 rpm) and a constant travel speed of 120 mm/min. Thermocouples were embedded at three representative positions on the advancing side of the FSW joint to record the temperature histories. The friction stir welded joints were trans-sectioned for microstructural and hardness characterization. The mechanical properties of the FSW joints were evaluated by means of uniaxial tensile tests and Charpy V-notch impact tests at room temperature. In addition, based on ABAQUS code, a full 3D finite element (FE) model was developed to simulate the temperature field during the FSW process. The results show that the peak temperature calculated by FE model in the stir zone increases with tool rotation rates. A superior comprehensive mechanical performance of the FSW joints has been achieved at a moderate tool rotation rate of 1200 rpm. The peak temperature calculated by FE model in this case is 495 °C, and the joint efficiency is up to 90.2 %.